Severe Acute Pancreatitis Caused by Gallstones in a Young Adult - Ummi Maimunah; Inne Tria Ramafita (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Acute pancreatitis is a pancreatic exocrine disorder consisting of various degrees of inflammation and is correlated with the parenchymal gland's damage due to auto-digestion of pancreatic enzymes. One of the causes of acute pancreatitis is gallstones. Acute pancreatitis has a typical clinical picture of abdominal pain with sedentary and blunt characteristics located in the epigastrium or periumbilical and often radiates to the back or chest, waist, and lower abdomen. Here presented a case of a 20-year-old male diagnosed with severe acute pancreatitis caused by gallstones who experienced various complications including acute necrotizing pancreatitis, colon perforation that caused generalized peritonitis and fistulation, as well as sepsis. The patient felt the main complaints, including intermittent abdominal pain, decreased appetite, nausea, and weakness. The treatment given is adequate conservative therapy and surgery for fluid and abscesses drainage, correction of fistulations, and perforation of hollow organs.